Physiological and sanitary quality of soybean seeds in response to harvest delay - Carlos Henrique Conceição Sousa; Alan Mario Zuffo; Ricardo Mezzomo; Leandra Matos Barrozo; Fábio Steiner; Mohamed A. El-Tayeb; Hamada AbdElgawad; Charline Zaratin Alves (Revista Ciência Agronômica)
ABSTRACT Delays in soybean harvesting can limit seed viability and vigor. In this study, soybean cultivar seeds’ physiological and sanitary quality was evaluated in response to harvest delay. The experimental design used was completely randomized blocks, arranged in a split-plot scheme, with three replicates. The plots were represented by the cultivation of two soybean cultivars (BMX Bônus IPRO and BMX Olimpo IPRO), while the subplots were represented by three harvest times [0, 7, 14 days after the seed’s full maturity (stage R8)]. The following characteristics of the physiological and sanitary quality of the seeds were measured: water content, plant emergence, total dry matter, germination, accelerated aging, electrical conductivity, and seed health. The delay in the soybean harvest affects the seeds’ physiological and sanitary quality. Seeds harvested seven days after full maturity have a higher incidence of Aspergillus flavus and Macrophomina sp. In comparison, seeds harvested 14 days after full maturity have a higher incidence of Phomopsis sp. and Fusarium sp.